Inhibition of xpt Guanine Riboswitch by a synthetic nucleoside analog - Swapan S. Jain; Emily C. McLaughlin; Gabriel G. Perron; Mallikarjunachari Uppuladinne; Seoyoung Kim; Katherina Gindinova; Silvie H. Lundgren; Liad Elmelech; Uddhavesh Sonavane; Rajendra Joshi; Korrapati Narasimhulu (PLoS ONE, 2025)
Riboswitches are structured elements predominantly found in the 5’-untranslated region of many bacterial mRNA. These noncoding RNA regions play a vital role in bacterial metabolism and overall function. Each riboswitch binds to a specific small molecule and causes conformational changes in the mRNA leading to regulation of transcription or translation. In this work, we have synthesized SK4, a novel nucleoside analog that binds to the guanine riboswitch mRNA of the xanthine phosphoribosyl transferase gene in Bacillus subtilis and terminates transcription of the riboswitch mRNA to a greater extent than the native ligand guanine. Molecular dynamics simulations of SK4 with riboswitch mRNA reveal an overall stable complex with additional bonding interactions in comparison to guanine. Our work with SK4 demonstrates that specific genes in bacteria can be effectively controlled by ligand analogs, providing an alternative mechanism to regulate the function of bacteria.